La Planificación Microcurricular de Lengua y Literatura y la guía del Currículo Priorizado con Énfasis en Competencias en la Unidad Educativa “Lauro Damerval Ayora” - Pintado Castillo, Diana Julissa (2024)
Planning, microplanning and its execution in class depend largely on the way in which its components and procedures adopt the guidelines of the Prioritized Curriculum with Emphasis on Competencies. The research studies microplanning and class execution in the context of secondary education. The methodological approach is qualitative in nature, the process of which was organized in two phases: the first includes the comparative analysis between Planning and the current Curriculum through a checklist in which the relationship with the Prioritized Curriculum with Emphasis on Competencies was reviewed; The second phase involves class observation using an assessment rubric that allowed examined the quality of the class following the guidelines of the current Curriculum. The data collected through the application of the instruments led us to the following results. In the first phase, the results indicate that the Microcurricular Planning only meets with the disciplinary component, although the context, Curriculum, language focus, among others, required it, it is not planned for the interdisciplinary components, students with specific educational needs and hours of teaching support; The results of the second phase based on class observation reveal that the applied methodologies do not follow an organized learning process and these consist only of the transcription of texts. In certain cases, in Planning, a disconnection is observed among the learning objective, skill with performance criteria and the evaluation indicator. Likewise, both in Planning and in class execution there is no incorporation of the Curriculum competencies into the educational process.